Edukasi Konsumsi Gula, Garam, Dan Lemak Sebagai Upaya Pencegahan Sindrom Metabolik - Nur Pelita Sembiring; Novfiri Syuryadi; Yanti Ernalia; Tahrir Aulawi (Universitas Lancang Kuning, 2022)
KExcess levels of sugar, salt and fat consumption due to lack of knowledge are increasing every year and have an impact on the high incidence of metabolic syndrome. It is important to share nutrition information to the Darul Amal Mosque community in Pekanbaru, which is a category of adult and elderly population who are at risk of developing metabolic syndrome. Weight and height were measured to obtain the Body Mass Index (BMI) value as indicator nutritional status. Education is done using video media, posters, and infocus media. The participants had nutritional problems, being thin (10%), pre-obese (10%), obese I (25%), and Obes II (15%). The post test results showed an increase in nutritional knowledge in the good category from 60% to 95%. Meanwhile, the nutritional knowledge in the less category decreased from 40% to 5%. Education went well and suggested to continue with different topics and be accompanied by practice.